Regulation of Glucose and Lipid Metabolism by Long Non-coding RNAs: Facts and Research Progress - Zhang, Tie-Ning; Wang, Wei; Yang, Ni; Huang, Xin-Mei; Liu, Chun-Feng (Frontiers in Endocrinology, 2020)
Long noncoding RNAs (lncRNAs) are a type of noncoding RNA with a length that exceeds 200 nucleotides. Previous studies have shown that lncRNAs play an important role in the pathogenesis of various diseases. Research in both animal models and humans has begun to unravel the profound complexity of lncRNAs and demonstrated that lncRNAs exert direct effects on glucose and lipid metabolism both in vivo and in vitro. Such research has elucidated the regulatory role of lncRNAs in glucose and lipid metabolism in human disease. lncRNAs mediate glucose and lipid metabolism under physiological and pathological conditions and contribute to various metabolism disorders. This review provides an update on our understanding of the regulatory role of lncRNAs in glucose and lipid metabolism in various diseases. As our understanding of the function of lncRNAs improves, the future is promising for the development of new diagnostic biomarkers that utilize lncRNAs and treatments that target lncRNAs to improve clinical outcomes.